Սրվեղի վանական համալիրը - Սաֆարյան, Մերի
Монастырский комплекс Срвег (XIII-XIV вв.) расположен в общине Айгеовит Тавушской области РА. В рамках государственной программы по фиксации и реставрации памятника экспедиция «Научно-исследовательского центра историко-культурного наследия» в 2021-2022 гг. провела работы по очистке и благоустройству и частичные исследовательские раскопки на территории монастыря. Далее последовала совместная работа архитекторов-реставраторов, инженеров-строителей и геологов под руководством Оганнеса Санамяна над проектом стабилизации и восстановлении комплекса. Подводя итог, можно сказать, что проведя раскопки на территории монастырского комплекса, мы полностью выполнили поставленные перед ними задачи. В частности, мы выяснили, что главная церковь Св. Креста стоит на естественной скале и что обвалы – результат землетрясений, а не мягких, рыхлых оснований. Это обстоятельство значительно облегчит работы по восстановлению церкви. The Srvegh monastery complex is located in the Aygehovit community of the Tavush region of the Republic of Armenia. It is dated to the 13th century. Within the framework of the state program for the fixation and restoration of the monument, in 2021–2022 the expedition of the “Scientific Research Center for Historical and Cultural Heritage” carried out cleaning and improvement work and partial excavations on the territory of the monastery. This was followed by a joint work of architectsrestorers, civil engineers and geologists under the supervision of Hovhannes Sanamyan within the project of stabilizing and restoring the complex. Summing up, we can say that the excavations completely fulfilled the tasks assigned to them. In particular, we found out that the main Holy Cross church stands on a natural rock and that the collapses are the result of earthquakes, and not of soft, loose foundations. This will significantly facilitate the restoration process. In a short time, in addition to the cleaning work, we also carried out partial excavations. The finds suggest that the monastery of Srvegh had a large community in the High Middle Ages and was very famous like its contemporaries Kirants‘ and Makaravank‘.
Keywords: Հայոց եկեղեցու պատմություն